IMPLEMENTATION OF EFFECTIVE HUMAN RESOURCE MANAGEMENT POLICIES IN IMPROVING ORGANIZATIONAL PERFORMANCE IN THE INDUSTRIAL ERA 5.0 - Suprayitno (Adisam Publisher, 2025)
In the context of Industry 5.0, this study intends to examine how well human resource management practices are being implemented in terms of enhancing organizational performance. The fusion of cutting-edge technologies with a human-centered approach, like automation, the Internet of Things, and artificial intelligence, characterizes this period. In facing these changes, organizations need to adopt human resource policies that are able to accommodate technological developments, as well as improve employee welfare and productivity. The study's findings show that human resource policies that focus on personalization, work flexibility, skill enhancement through reskilling and upskilling, and collaboration between humans and technology are able to significantly improve organizational performance. In addition, innovative leadership support and an adaptive organizational culture additionally contribute significantly to the effective execution of this policy. As a result, this study highlights how crucial it is to have efficient human resource management to meet obstacles and seize opportunities in the Industry 5.0 era in order to achieve more optimal organizational performance.